2012
DOI: 10.21452/rde.v14i26.1761
|View full text |Cite
|
Sign up to set email alerts
|

A Eficiência Dos Gastos Municipais Na Geração De Bem-Estar Na Região Metropolitana De São Paulo

Abstract: O objetivo deste artigo é analisar a eficiência dos municípios da Região Metropolitana de São Paulo (RMSP) na geração de bem-estar em 2000. Os procedimentos envolvem três etapas. A primeira é a identificação de indicadores de bem-estar que sejam convergen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
2
1
3
Order By: Relevance
“…Regarding the 'environment' external contingency factor, the human development approach is geared towards people, their capabilities and opportunitiesnot only the resources or income they can generateso that the essence is in human beings, not in economic growth (Silva, Silva, Souza, & Silva, 2015). Additionally, the search for maximizing well-being with available resources is one of the main challenges for public policy managers and citizens' interests (Scarpin & Slomski, 2007;Silva, Kuwahara, & Maciel, 2012), and this is due to the concern with public policies from the social sector, such as health and education (Silva et al, 2015). Thus, the Human Development Index -Municipal (HDI-M) is a relevant social development assessment metric, as it is the best-known measure of human development (Torres, Ferreira, & Dini, 2003); thus, hypothesis 1 is:…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Regarding the 'environment' external contingency factor, the human development approach is geared towards people, their capabilities and opportunitiesnot only the resources or income they can generateso that the essence is in human beings, not in economic growth (Silva, Silva, Souza, & Silva, 2015). Additionally, the search for maximizing well-being with available resources is one of the main challenges for public policy managers and citizens' interests (Scarpin & Slomski, 2007;Silva, Kuwahara, & Maciel, 2012), and this is due to the concern with public policies from the social sector, such as health and education (Silva et al, 2015). Thus, the Human Development Index -Municipal (HDI-M) is a relevant social development assessment metric, as it is the best-known measure of human development (Torres, Ferreira, & Dini, 2003); thus, hypothesis 1 is:…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Regarding their use, [37] used development and public expenditure indicators to measure the public efficiency of welfare. Their conclusions showed that IFDM plays an important role in public service evaluations.…”
Section: Municipal Developmentmentioning
confidence: 99%
“…Ferreira (2004) denomina tal movimento por Municipalização, a qual apresenta uma vantagem em sua composição, dado a proximidade entre o gestor e o cidadão, o que permite uma melhor cap-tação das preferências da sociedade (Silva 2006). Mais especificamente, como ressaltado por Silva (2012), a predominância do interesse é o princípio geral que norteia a repartição de competência entre as entidades do Estado Federal. Nesta divisão cabem à União as matérias e questões de interesse nacional; aos Estados cabem os assuntos de interesse regional; e aos municípios, os de interesse local.…”
Section: Instituições E Municipalização No Brasilunclassified
“…A Municipalização permitiu que tais entes subnacionais obtivessem autonomia e competência para legislar em assuntos de interesse local. Tal autonomia se sustenta em quatro capacidades: de autogoverno, de auto-organização, de autoadministração e a capacidade normativa própria (Silva 2012). De acordo com Senem e Teza (2015), as limitações administrativas do município são provenientes de algumas normas, como a Lei Orgânica, o Plano Diretor, o Código de Obras e Edificações, o Código de Posturas dentre outros, incluindo também as leis específicas.…”
Section: Instituições E Municipalização No Brasilunclassified
See 1 more Smart Citation